Zooplankton characterisation of Pampean saline shallow lakes, habitat of the Andean flamingoes - Yamila S. Battauz; Susana B. José de Paggi; Juan C. Paggi; Marcelo Romano; Ignacio Barberis (Journal of Limnology, 2013)
The lowland saline shallow lakes in the Pampa de las Lagunas (Argentina), constitute an important habitat for flamingoes Phoenicopterus chilensis Molina and Phoenicoparrus andinus (Philippii). Little is known about the zooplankton communities of these systems, and their relationships with the temporal and spatial distribution of flamingoes. Ten shallow lakes in the Pampean region were studied in 2009 and 2010 winters, and in 2010 summer in order to assess the abundance, size and biomass of zooplankton and the density of flamingoes populations. Zooplankton was represented by 28 species. Copepods and cladocerans were dominant when salinity was lower (winter and summer of 2010). Seasonal changes were recorded in composition and mean abundance of zooplankton. Significant differences were  observed in mean size of zooplankton showing a negative relationship with the abundance of P. chilensis, which can be interpreted as a consequence of the selective flamingoes zooplanktophagy feeding upon the largest members of this community. Other community parameters, such as abundance, biomass, diversity and composition, did not show an apparent direct relationship with the presence or abundance of flamingoes.